Effect of Capital, Labor, Hours of Work and Length of Business on Toll Counter Income in Palangka Raya City - Ahmad Rizani; Karmen Marpaung; Ega Dwi Maharani (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2021)
This study aims to determine the effect of capital, labor, working hours, and length of business on the income of the pulse counter in the city of Palangka Raya. The research method used in this research is a quantitative method. Data collection techniques in the form of a questionnaire (questionnaire) with sampling using purposive sampling as many as 50 respondents. The data analysis technique used is multiple linear regression analysis and hypothesis testing using the IBM SPSS 25 program. The results show that capital, working hours, and length of business have a partial effect on pulse counter income in Palangka Raya City while the labor variable has no significant effect. partial to pulse counter income in Palangka Raya City. But simultaneously all variables have a significant effect on the income of the pulse counter business in Palangka Raya City